2015
DOI: 10.1111/pce.12637
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal patterns in Scots pine stem oleoresin pressure in a boreal forest

Abstract: Coniferous tree stems contain large amounts of oleoresin under positive pressure in the resin ducts. Studies in NorthAmerican pines indicated that the stem oleoresin exudation pressure (OEP) correlates negatively with transpiration rate and soil water content. However, it is not known how the OEP changes affect the emissions of volatile vapours from the trees. We measured the OEP, xylem diameter changes indicating changes in xylem water potential and monoterpene emissions under field conditions in mature Scots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
6
17
0
Order By: Relevance
“…The observed growing season monthly mean monoterpene emission rates (1.6-2.4 ng m −2 s −1 ) were in the same range as previously reported lower stem bark monoterpene emission rates in non-stressed conditions from mature Norway spruce (Ghimire et al, 2016) and Scots pine trees (Rissanen et al, 2016), while also considerably higher emissions have been reported e.g., from Maritime pine stems (up to 99 ng m −2 s −1 ; Staudt et al, 2019). Upscaling to the stand level and assuming that all stems would be of an equal size, the average monoterpene emission rate from pine stems was 6.8 mg ha −1 h −1 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed growing season monthly mean monoterpene emission rates (1.6-2.4 ng m −2 s −1 ) were in the same range as previously reported lower stem bark monoterpene emission rates in non-stressed conditions from mature Norway spruce (Ghimire et al, 2016) and Scots pine trees (Rissanen et al, 2016), while also considerably higher emissions have been reported e.g., from Maritime pine stems (up to 99 ng m −2 s −1 ; Staudt et al, 2019). Upscaling to the stand level and assuming that all stems would be of an equal size, the average monoterpene emission rate from pine stems was 6.8 mg ha −1 h −1 .…”
Section: Discussionsupporting
confidence: 87%
“…Tree stems provide support and conductive tissues for the tree. In addition to these structural features, conifer stems are important in possessing large storages of defense compounds, mainly consisting of a complex mixture of resins that are located in specialized resin canals or ducts (e.g., Phillips and Croteau, 1999;Trapp and Croteau, 2001;Rissanen et al, 2016). One of the main defense mechanisms of conifers against herbivores and pathogens relies on volatile organic compounds (VOC), especially terpenoids in resins (Phillips and Croteau, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The measurements from stem chambers followed principally the same protocol as that from shoot chambers, with the exception that between measurements, the chamber was flushed with ambient air at the rate of approximately 0.4 L/min in order to prevent accumulation of CO 2 , moisture, and VOCs, for example. The structure of the stem chambers, measurements, and calculations are presented in more detail by Vanhatalo et al and Rissanen et al (2016). The lowest chamber was at 7 m, well below the living canopy, where the stem diameter (1999) and by Kolari et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Soil water content data can improve MEGAN's modeling results by the use of its simple drought 453 algorithm, although recent results show that even when soil moisture data is available there is 454 still room for model improvement (Seco et al, 2015) and that atmospheric demand for water can 455 make VPD more limiting for ecosystem functioning than soil moisture supply (Novick et al, 456 2016). Furthermore, novel findings suggest that emissions of monoterpenes from pine oleoresin 457 storage pools may also be regulated by the xylem water potential and not only by the ambient 458 temperature and light conditions (Rissanen et al, 2016). These facts highlight the need for 459 comprehensive availability of environmental and physiological information in order to gain 460 insight into our physiological understanding and improve our BVOC emission modeling 461 capability.…”
Section: Modeled Voc Fluxes 347mentioning
confidence: 99%